Physical Characteristics of Egg Yolk Granules and Effect on Their Functionality - Beatrice Mofoluwaso Oladimeji; Ronald Gebhardt (Foods, 2023)
Eggs are among the most nutritious foods in the world, a versatile ingredient in many food applications due to their functional attributes such as foaming, emulsifying, and coloring agents. Many studies have been reported on egg yolk fractionation and characterization in the last decade because of its nutritional and health benefits, especially egg yolk granules. This has led to the development of new food products and packaging materials. However, the influence of their physical characteristics during processing significantly impacts the functionality of yolk granules. In this overview, the egg yolk, the granule fraction’s separation, fractionation, components, and molecular protein structure are first presented. Secondly, recent studies on egg yolk granules published over the past decade are discussed. Furthermore, the application of the granules in different industries and current specific scientific challenges are discussed. Finally, it simplifies the changes in the physical characteristics of the granules during different treatment methods and the impact on the functionalities of the resulting products in the food (emulsifiers, edible films), pharmaceutical, and health (encapsulation systems and biosensors) sectors.